Strömungsmechanik zwischen Mathematik und Ingenieurwissenschaft Felix Kleins Hydrodynamikseminar 1907/08 - Eckert, Michael (Hamburg University Press, 2019)
Hydrodynamics was long considered a subject for mathematicians and theoretical physicists. Although the engineering subject of hydraulics offers useful formulae for many practical problems, these could only be justified empirically. In the winter semester of 1907/08, the mathematician Felix Klein organised a seminar at Göttingen University with the declared aim of bridging this gap. The participants' contributions show how the gap between theoretical hydrodynamics and practical hydraulics was bridged with modern fluid mechanics.